Quo Vadis Object of Civil Court of Justice Disputes After Government Administrative Law : Regional House of People’s Representative Decision Concerning Dismissal Recomendation for Regional Chief/Vice Chief - Nur Sayekti; Isharyanto Isharyanto (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2020)
The presence of Act Number 30 Year 2014 concerning Government Administration has presented significant developments in the context of Civil Court of Justice in Indonesia. One thing that is very highlighted after the enactment of the Law is that the definition of state administrative decisions which are only interpreted as a decision issued by a state administration official in this case is the executive body and is concrete, individual and the final becomes a state administrative decision issued by the executive, legislative and judicial institutions and has the additional nature of factual action. One of the cases that the author examined in this paper is related to the decision of the Gorontalo’s legislative assemblythrough Gorontalo’s legislative assembly decision Number 29 / KEP / DPRD / IX / 2017 which basically contained the impeachment of the Gorontalo District Deputy Regent. In accordance with the existing provisions, the characteristics of the action are in accordance with the criteria set out in the provisions of the Act, but from a substantive point of view is still debated in the theoretical level both with regard to the criteria of officials who issue decisions in this case the Regional People's Representative Assembly (institutions) and the nature of decisions that are not final as stipulated in the provisions of the Act of Local Government. Keywords: the object of civil court of justice disputes; regional house of people's representative; quo vadis